Integration of fuzzy AHP and fuzzy TOPSIS for green supplier selection of mindi wood raw materials - Viola Indira Ramadhanti; Farida Pulansari (Universitas Serang Raya, 2022)
The current industrial development is related to increasing global action and public awareness of environmental issues with Sustainable Development Goals (SDGs). It makes the implementation of green supply chain management on Green Supplier Evaluation and Selection (GSES) more appreciated because it can affect the company's environmental performance. Companies that can improve their environmental performance will be able to increase their competitive advantage and have an impact on increasing revenue, market share, and a more positive green image of the company. Currently, there is no research about green supplier selection in the furniture industry, especially in Indonesia. So, it is necessary to research the industry because it hugely affects environmental performance. One of the companies engaged in the furniture industry is X company. They are selecting their suppliers only based on the ownership of the environmental certification of each supplier and the quality of the raw materials. Environmental criteria such as the green image in the community and environmental competency have not been considered. On the one hand, X company also wants to realize its mission of environmental sensitivity. This study aims to select the best green supplier of mindi wood raw materials by integrating fuzzy AHP and TOPSIS because these methods can make practical multicriteria decisions and obtain more valid results. The results obtained indicate that the 8th green supplier has the highest preference value of 0.777 so it is called the best alternative for mindi wood raw materials.